Representasi Maskulinitas Iklan Joe Taslim X Fadil Jaidi Versi â€œSiapakah BA Head and Shoulders Selanjutnya?â€ - Findy Pattimah; Johantan Alfando WS (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
The purpose of this research is to analyze the representation of masculinity and the meaning of myths contained in Joe Taslim X Fadil Jaidi advertisement for the version â€œSiapakah BA Head & Shoulders Selanjutnyaâ€. This research method uses interpretive qualitative methods with Roland Barthes' Semiotics analysis technique. The focus of this research is the characteristics of masculinity proposed by Beynon. The object of this research is the scenes in the advertisement for Joe Taslim X Fadil Jaidi's version of "Who is the Next BA Head and Shoulders?" representing masculinity. The results obtained in this study can be concluded that Joe Taslim X Fadil Jaidi advertisement version "Siapakah BA Head & Shoulders Selanjutnya" has a relationship with masculinity traits, no sissy stuff, be a big wheel, be a sturdy oak, give em hell, new man as narcissist, male nature that is macho and hooliganism, and metrosexual man who glorifies fashion but in terms of masculinity, the new man as nurturer Joe Taslim and Fadil Jaidi do not show their fatherly side and are involved in the domestic arena.